Modularity among horse mandibles: a study in the Araucan breed - Arcesio Salamanca-Carreño; Pere M. Parés-Casanova; Oscar Mauricio Vélez-Terranova; Nestor Ismael Monroy-Ochoa; René A. Crosby-Granados (Journal of Applied Animal Research, 2022)
The concepts of integration and modularity refer to the degree of covariation between the components of a biological structure. Components that covariate strongly, but are relatively independent of other modules, are called morphological modules. Morphological integration is understood as the coordinated morphological variation of these components as a functional unit. In mandible case, four modules have been defined based on their differential embryonic origin: alveolar, basal body, coronoid and condylar. The aim was to test these four modular mandible bases using geometric morphometric techniques. The hypothesis of modularity of mandibular development, based on differential embryonic origins, was tested using digital pictures of hemimandibles in lateral form from 26 Araucan horses for those modules. Subsequently, the level of morphological integration between the modules defined above was evaluated using eight landmarks and 65 semi-landmarks, through an analysis of paired blocks of least squares. The divisions between those units presented a modular foundation and the respective level of morphological integration between all considered units. The results of our modular and integrative analysis can be very useful for the comparative study of adaptive processes of other equine breeds.